Modeling Neuropsychiatric and Neurodegenerative Diseases With Induced Pluripotent Stem Cells - LaMarca, Elizabeth A.; Powell, Samuel K.; Akbarian, Schahram; Brennand, Kristen J. (Frontiers in Pediatrics, 2018)
Human induced pluripotent stem cells have revolutionized our ability to model neuropsychiatric and neurodegenerative diseases, and recent progress in the field is paving the way for improved therapeutics. In this review, we discuss major advances in generating hiPSC-derived neural cells and cutting-edge techniques that are transforming hiPSC technology, such as 3D "minibrains" and CRISPR. We examine specific examples of how hiPSC-derived neural cells are being used to uncover the pathophysiology of schizophrenia and Parkinson's Disease, and consider the future of this groundbreaking research.